The adaptation and uptake evaluation of an SMS text message smoking cessation programme (MiQuit) for use in antenatal care - Naughton, Felix; Cooper, Sue; Bowker, Katharine; Campbell, Katarzyna; Sutton, Stephen; Leonardi-Bee, Jo; Sloan, Melanie; Coleman, Tim (BMJ Publishing Group Ltd, 2015)
Objectives: To adapt a tailored SMS text message smoking cessation intervention (MiQuit) for use without active health professional endorsement in routine antenatal care settings, to estimate ‘real world’ uptake and test the feasibility of its use. Design: Single-site service evaluation. Setting: A Nottinghamshire (UK) antenatal clinic. Participants: Pregnant women accessing the antenatal clinic (N=1,750) over 6-months. Intervention: A single-sheet A5 leaflet provided in the women’s maternity notes folder describing the MiQuit text service. Similar materials were left on clinic desks and noticeboards. Outcome measures: MiQuit activation requests and system interactions were logged for two timeframes: 6 months (strict) and 8 months (extended). Local Hospital data were used to estimate the denominator of pregnant smokers exposed to the materials. Results: During the strict and extended timeframes, 13 and 25 activation requests were received, representing 3% (95% CI 2-5%) and 4% (95% CI 3-6%) of estimated smokers respectively. Only 11 (44%) of the 25 requesting activation sent a correctly formatted initiation text. Of those activating MiQuit, and invited to complete tailoring questions (used to tailor support), six (67%) completed all 12 questions by text or website and five (56%) texted a quit date to the system. Of the eleven activating MiQuit, five (45%, 95% CI 21-72%) stopped the programme prematurely. Conclusions: A low intensity, cheap cessation intervention promoted at very low cost, resulted in a small but potentially impactful uptake rate by pregnant smokers.